Effects of Stretching or Strengthening Exercise on Spinal and Lumbopelvic Posture: A Systematic Review with Meta-Analysis - Konstantin Warneke; Lars Hubertus Lohmann; Jan Wilke (SpringerOpen, 2024)
Abstract Background Abnormal posture (e.g. loss of lordosis) has been associated with the occurrence of musculoskeletal pain. Stretching tight muscles while strengthening the antagonists represents the most common method to treat the assumed muscle imbalance. However, despite its high popularity, there is no quantitative synthesis of the available evidence examining the effectiveness of the stretch-and-strengthen approach. Methods A systematic review with meta-analysis was conducted, searching PubMed, Web of Science and Google Scholar. We included controlled clinical trials investigating the effects of stretching or strengthening on spinal and lumbopelvic posture (e.g., pelvic tilt, lumbar lordosis, thoracic kyphosis, head tilt) in healthy individuals. Effect sizes were pooled using robust variance estimation. To rate the certainty about the evidence, the GRADE approach was applied. Results A total of 23 studies with 969 participants were identified. Neither acute (d = 0.01, p = 0.97) nor chronic stretching (d=-0.19, p = 0.16) had an impact on posture. Chronic strengthening was associated with large improvements (d=-0.83, p = 0.01), but no study examined acute effects. Strengthening was superior (d = 0.81, p = 0.004) to stretching. Sub-analyses found strengthening to be effective in the thoracic and cervical spine (d=-1.04, p = 0.005) but not in the lumbar and lumbopelvic region (d=-0.23, p = 0.25). Stretching was ineffective in all locations (p > 0.05). Conclusion Moderate-certainty evidence does not support the use of stretching as a treatment of muscle imbalance. In contrast, therapists should focus on strengthening programs targeting weakened muscles.